Xylose Assimilation for the Efficient Production of Biofuels and Chemicals by Engineered Saccharomyces cerevisiae. Issue 4 (13th November 2020) - Sun, Liang; Jin, Yong‐Su
Abstract: Microbial conversion of plant biomass into fuels and chemicals offers a practical solution to global concerns over limited natural resources, environmental pollution, and climate change. Pursuant to these goals, researchers have put tremendous efforts and resources toward engineering the yeast Saccharomyces cerevisiae to efficiently convert xylose, the second most abundant sugar in lignocellulosic biomass, into various fuels and chemicals. Here, recent advances in metabolic engineering of yeast is summarized to address bottlenecks on xylose assimilation and to enable simultaneous co‐utilization of xylose and other substrates in lignocellulosic hydrolysates. Distinct characteristics of xylose metabolism that can be harnessed to produce advanced biofuels and chemicals are also highlighted. Although many challenges remain, recent research investments have facilitated the efficient fermentation of xylose and simultaneous co‐consumption of xylose and glucose. In particular, understanding xylose‐induced metabolic rewiring in engineered yeast has encouraged the use of xylose as a carbon source for producing various non‐ethanol bioproducts. To boost the lignocellulosic biomass‐based bioeconomy, much attention is expected to promote xylose‐utilizing efficiency via reprogramming cellular regulatory networks, to attain robust co‐fermentation of xylose and other cellulosic carbon sources under industrial conditions, and to exploit the advantageous traits of yeast xylose metabolism for producing diverse fuels and chemicals. Abstract : Production of diverse chemicals from xylose is indispensable for the implementation of lignocellulosic biomass‐based bioeconomy. This review summarizes recent advances in metabolic engineering of yeast to address bottlenecks of xylose assimilation and to enable simultaneous co‐utilization of xylose and other cellulosic substrates. This review also highlights distinct characteristics of yeast xylose metabolism that can be harnessed to produce various chemicals.